Knowledge to Action: How Digital Financial Literacy Shapes Investment Decisions of Generation Z Through Fintech - Candera, Mister; Safitri, Ervita; RZ Muhammad Ferdi Saputra; Kasuwara, Citra (Universitas Muhammadiyah Malang, 2026)
Purpose: This study aims to examine how digital financial literacy influences investment decision-making among Generation Z, with a focus on the mediating role of financial technology. Methodology/approach: This study uses a quantitative approach with data collection through questionnaires distributed to 254 Generation Z respondents in South Sumatra who actively use FinTech-based investment platforms. Data analysis was conducted using the Structural Equation Modelling (SEM-PLS) method to test the relationship between hypothesized variables Findings: The results show that digital financial literacy, represented by knowledge and attitude does not directly influence investment decisions (investment intention and action). Indirectly, digital financial literacy, represented by knowledge and attitude has a significant influence on investment decisions (investment intention and action) mediated by the use of financial technology. FinTech acts as a bridge that transforms knowledge into investment behavior. Practical implications: This research contributes to the development of digital financial behavior literature as well as practical implications for policymakers, educators, and FinTech companies in designing financial literacy programs and digital platforms that support responsible investment among the young digital generation. Originality/value: This study fills a gap in the literature regarding the link between digital financial literacy and investment decisions in the context of FinTech use.